The archives as public entities in Cuba: an analysis from its legal framework - Delgado López, Yorlis (Revista General de Información y Documentación, 2019)
The Archives are public entities with an extremely important social function, since they retain the documentation generated by a country, a territory, an entity, a scientific discipline, etc. At present, these objectives are valued more towards the preservation of citizens' rights or / and as a guarantor of the management and accountability of the administration, regardless of the age of the document they preserve and the historicist criteria that are fencing This reality has an impact on legislation that in the case Cuba becomes since the 18th century. This article intends to evaluate the legal protection of archives in Cuba as public entities of the Government from a systemic vision of the subject. An updated analysis on the subject is obtained; and delves into how this legal good (categorization assumed in the essay) has been seen in Cuba by archival legislation, from the colonial stage to the present.
Keywords: Archives; Public entities; Legal protection; Archival legislation; Cuba